Dynamics of Classical Islamic Theology: Rationalism, Authority, and Sectarian Reception in Southeast Asian Muslim Societies - Mohammad Fahmy Bin Rapaee; Rezky Pratama Marsudi; Muhammad Firdaus; Muhammad Yaub Yakub (Islam and Social Sciences Review, 2025)
This study examines the dynamics of classical Islamic theology through a comparative analysis of five major theological schools Ashʿarism, Murjiʾism, Shiʿism, Muʿtazilism, and Kharijism—and their contemporary reception in Indonesia and Malaysia. Islamic theology (ʿilm al-kalām) emerged from political conflicts and intellectual debates following the death of the Prophet Muhammad, particularly concerning political authority, faith, divine justice, and the relationship between reason and revelation. This study employs a qualitative library-based approach using descriptive-analytical and comparative methods. Data from primary and secondary sources were analyzed through comparative content analysis. The findings show that each theological school reflects a distinct doctrinal orientation. Kharijism adopted an exclusive stance by excommunicating Muslims who committed major sins, while Murjiʾism promoted a more inclusive approach by deferring judgment to God. Shiʿism emphasized imāmah as the basis of religious and political authority, whereas Muʿtazilism prioritized rational inquiry and human agency. In contrast, Ashʿarism reconciled reason and revelation and later became the dominant theological framework in Sunni Islam. The study also demonstrates that the reception of these traditions in Southeast Asia is shaped by socio-political structures and state religious policies. Indonesia tends to be more pluralistic and accommodative, while Malaysia institutionalizes Sunni Ashʿarism as its official theological orientation. This study argues that classical Islamic theological discourses remain relevant for promoting religious moderation, intellectual pluralism, and inter-sectarian dialogue in contemporary Muslim societies.